PELUANG DAN TANTANGAN PENGEMBANGAN PERUSAHAAN RINTISAN BERBASIS KOPERASI PEKERJA (STARTUP COOP) DI INDONESIA - Aulia Rachman, Muhammad; Jayusman, Jayusman; Noviarita, Heni (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2021)
A workers' cooperative (Startup coop) was born to respond to the trend of private startup business. The Indonesian Consortium for Cooperatives Innovation (ICCI) as a forum that initiates and develops coop startups has successfully incubated more than 10 companies. The purpose of this study is to determine the opportunities and challenges of coop startup development in Indonesia. Research method using literature study. The results of the study found that coop startup opportunities are very promising with a modernized cooperative model and various cooperative platforms in the digital era, so that it invites the younger generation, especially the millennial generation, to enter the world of cooperatives and develop cooperatives progressively and organically in Indonesia in the following years. A very clear challenge is related to regulations and the basis of the economic constitution used by Indonesia regarding the basis of legal products regarding startup coops that must adhere to a populist economy in accordance with the foundations laid by the founding fathers.